Hereditary Breast Cancer Risk Analysis in Uninsured Mexican-Origin Women Living in the U.S.–Mexico Border Region. (September 2019) - Salinas, Jennifer J.; Roy, Renet; Dwivedi, Alok K.; Shokar, Navkiran K.
Purpose: This article describes the risk of hereditary breast cancer (HBC) in low-income Hispanic women living on the U.S.–Mexico border using the Pedigree Assessment Tool (PAT). Method: The PAT was administered as part of the El Paso and Hudspeth County Breast Cancer Education, Screening and NavigaTion program (BEST). Baseline data ( n = 1, 966) from this program was used to analyze risk factors for HBC. Analysis was conducted to determine significant covariates associated with the presence of any PAT risk factors. Results: The PAT identified 17% (95% CI [15%, 19%]) of the women in the study as having some risk of HBC. Having had a mammogram within 3 years was significantly associated with having any PAT risk factors (odds ratio [OR] = 1.79, p = .006). Women who immigrated to the United States during childbearing age (OR = 0.610, p = .009) or during peri/menopause (OR = 0.637, p = .024) were significantly less likely to have any PAT risk factors. Discussion: The PAT instrument detected a substantial pool of women who may be at risk for HBC. A significant proportion of these women were not up to date mammogram. Conclusions: The PAT is an effective tool to identify women at risk for HBC and encourage regular screening.